Isolation and Characterization of Fungi strains associated with Mycotoxin Production from Bambara (Vigna subterranea (L) verdc) nuts Recovered in Nigeria - Simeon Kolawole Odetunde; Stephen Oyedele Fapohunda; Segun Gbolagade Jonathan (Journal of Tropical Life Science, 2021)
Fungal contamination of food commodities is a global food security challenge that impacts negatively on the health of consumers. Mycotoxins are produced as secondary metabolites by some pathogenic fungi and may contaminate agricultural products while on the field or during harvesting and storage. A field survey was conducted in order to isolate and identify the mycotoxin producing fungal strains in Bambara nuts collected from major markets in eight States in Nigeria. Samples per site were pooled, processed and screened for the presence of mycotoxin-producing fungi by culture technique and intergenic spacer sequencing (ITS). Mycotoxin production was determined using thin layer chromatography (TLC) with scanning densitometer. Twenty-four producing fungal strains: Talaromyces pinophilus, Macrophomina phaseolina (6), Fusarium oxysporum (2), Aspergillus foetidus, Aspergillus flavipes, Rhizopus oryzae (2), Phanerochaete chrysosporium, Aspergillus flavus (2), Aspergillus terreus, Aspergillus awamori, Aspergillus welwitschiae, Rhizopus microsporus, Ceriporia lacerate and Fusarium verticillioides (accession numbers of MN42329-MN4233323) were identified from Bambara nuts. The genera Macrophomina were the most dominant. Some of the identified fungi are noted for the production of mycotoxins and mycotoxins exert toxic effects on animals and humans. The fungi associated to Bambara nut diseases were identified and can be taken as targets in varietal improvement of Bambara nut for resistance to fungal diseases in Nigeria.